Georgia Architectural and Historic Properties Survey of 116 Second Avenue, Valdosta, Ga., October 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 116 Second Avenue, Valdosta, Ga., October 1980. One story Georgian plan with hipped and multi-gabled roof. Shed porch with square posts. Exposed rafters. Central hall. Sits on brick piers. Clapboard. Double hung sash windows with 1/1 lights. Fair condition. Date of Construction: App. 1900-1910. Good example of central hall plan house. Not significant as part of a district because there are too many modern intrusions.
Georgia Architectural and Historic Properties Survey of 116 Second Avenue, Valdosta, Ga., October 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 79.1 MB (83,034,558 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)